Pengaruh Penggunaan Augmented Reality Terhadap Peningkatan Pemahaman Konsep IPA Anak Tunarungu Kelas VIII di SLB-B YPPLB Makassar - Azizah, Annisa Asyhiatul; Wizerti Ariastuti Saleh; St. Kasmawati; Awayundu Said (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the effectiveness of augmented reality media in improving the understanding of science concepts, especially the digestive system material, in deaf students of grade VIII at SLB-B YPPLB Makassar. The background of this study is the instability of students' understanding who have difficulty absorbing abstract material without the help of adequate visual media. Using a quantitative approach with the Single Subject Research (SSR) method with an A-B-A design, this study focuses on one subject with the initials Y through three stages: baseline 1 (A1), intervention (B), and baseline 2 (A2). Data were collected through observation, tests, and interviews, then analyzed using descriptive statistics. The results of the study showed a significant increase in each phase. In the baseline 1 (A1) condition, the subject's score was at 30 with a stable trend. After being given intervention using augmented reality media (B), the score increased to the range of 40 to 70. This increase continued in the baseline 2 (A2) phase with a score of 80 to 90 and a high level of stability. Based on the results of the analysis, it can be concluded that the application of augmented reality media has a positive and effective effect in improving the understanding of science concepts for deaf students at SLB-B YPPLB Makassar.